(untitled) - Most, Bernard (San Diego, CA, 1999)
A very, very boastful kangaroo brags that it can jump higher than anyone, but a teeny, tiny kangaroo cleverly wins the jumping contest.
Grades 1-2.
Keywords: Contests; Kangaroos; Fiction; Fiction